2015
DOI: 10.1093/oso/9780198716228.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Oxford Cases in Medicine and Surgery

Abstract: Oxford Cases in Medicine and Surgery, second edition, teaches students a logical step-by-step diagnostic approach to common patient presentations. This approach mirrors that used by successful clinicians on the wards, challenging students with questions at each stage of a case (history-taking, examination, investigation, management). In tackling these questions, students understand how to critically analyse information and learn to integrate their existing knowledge to a real-life scenario from start to finish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…These scenarios were formulated and designed from real-life clinical scenarios that the authors had encountered as ward-based junior doctors. The scenarios were then validated for accuracy and relevance with textbook analysis of case studies (11,12). These case studies were evaluated by a panel of two board-certified surgeons independently (AL and DD) with over 20 years of experience.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These scenarios were formulated and designed from real-life clinical scenarios that the authors had encountered as ward-based junior doctors. The scenarios were then validated for accuracy and relevance with textbook analysis of case studies (11,12). These case studies were evaluated by a panel of two board-certified surgeons independently (AL and DD) with over 20 years of experience.…”
Section: Methodsmentioning
confidence: 99%
“…Using a case study approach, each LLM will be prompted in three routine ward-based surgical situations to aid clinical decision-making. These scenarios were formulated based on real-life clinical scenarios and textbook case studies (11,12), with a final review by expert general surgeons. Responses were qualitatively evaluated for accuracy, safety, and effectiveness using a Likert scale (13).…”
Section: Introductionmentioning
confidence: 99%
“…By post op day 11 the graft uptake was 95% and wound healthy with minimal to no serous discharge with no microbial growth.DISCUSSIONVenous ulcers are the wounds that are mainly due to the improper functioning of venous valves & it is caused mostly due to the trauma. It is mainly associated with the varicose veins, a collection of small dark engorged superficial veins[6]. The ulceration mainly depends on pathophysiological abnormalities, anatomical changes & environmental influences.In this study we observed increased blood pressure that is caused by the venous ulcer, where venous valves exist to prevent the backflow of blood and raise the pressure in veins[7][8][9][10], where the other diseased conditions including immunosuppressive status also be the root cause for non-healing ulcer[9].…”
mentioning
confidence: 99%